Research progress of Traditional Chinese Medicine nursing of acute mastitis during lactation (哺乳期急性乳腺炎中医护理研究进展) - LI Yajing (李亚静); CHEN Hong (陈宏) (中西医结合护理)
Acute mastitis is a common disease in during lactation, affecting the breastfeeding of patients. Traditional Chinese Medicine nursing techniques have the advantages and characteristics of “simple, convenient, inexpensive and effective”, and have been widely used in clinical practice in recent years. This paper reviews the definition and characteristics of syndrome differentiation of acute mastitis, summarizes Traditional Chinese Medicine treatment of acute mastitis, discuss the prospect of the future development in research and clinical practice, and provided reference for development a diversified, targeted and integrated nursing plan. (急性乳腺炎是哺乳期患者常见疾病, 是影响母乳喂养的主要原因之一。中医护理技术具有“简、便、廉、验”的优势和特色, 近年来在临床应用广泛。本研究就急性乳腺炎的定义、辨证特点以及中医特色疗法进行综述, 对急性乳腺炎未来发展进行展望, 旨在为构建多元化、针对性、综合化的护理方案提供参考。)